Prevalence and Correlates of Internet Gaming Disorder Among an Advanced Level Student Population from Colombo, Sri Lanka - Minura Manjitha Manchanayake; Thalpe Guruge Madara Malsirini; Ashan Manelka Vithanage; Dushyanthi Jayawardene (University Library System, University of Pittsburgh, 2022)
Background: Internet Gaming Disorder (IGD) is rising in many low and middle-income countries owing to the increasing popularity of electronic gaming and technology availability among adolescents. However, the epidemiology of IGD in South Asia remains largely unknown. We aimed to determine IGD's prevalence and associations, including motivations for gaming, among a Sri Lankan school-going population. Methods: A cross-sectional study was conducted among Advanced Level students aged 16-18 attending four Colombo Educational Zone schools. Of the 412 randomly sampled recruits, 395 consenting participants filled a pretested questionnaire exploring gaming habits, motivations, and psychosocial factors. English and Sinhala versions of the Internet Gaming Disorder Scale Short-Form (IGDS9-SF) were used, and IGD was identified if ?5 items in the scale were endorsed. The Sinhala IGDS9-SF demonstrated acceptable internal consistency reliability, and its factorial validity was affirmed via Confirmatory Factor Analysis. Results: Among the sample, 81.5% (n=322) were gamers. A majority of these gamers preferred mobile gaming (64.0%) and Multiplayer Battle Royale games (27.0%). The prevalence of IGD was 5.06% (95% CI = 2.90-7.22) and was significantly higher (p<0.05) among males, who constituted 52.4% of the sample. Daily weekday gaming for ?6h, low involvement in student societies, poor relationship with parents, escape motive, and fantasy motive were positively associated with IGD, and the Competition motive was negatively associated with IGD in multivariable analyses. Conclusion: The prevalence of IGD was considerably high in our student population and is associated with specific motives, poor parent-child relationships, and low extra-curricular involvement.